Sistem Informasi Simpan Pinjam Multikoperasi Menggunakan Framework Laravel - Gabriela Minang Sari; Tristiyanto Tristiyanto; Muhammad Iqbal (Jurnal Komputasi, 2019)
The initial purpose of saving and loan cooperative is giving a financial solution for the members only. As time goes by, nowadays cooperative can provide finance support for small enterprise and public society. Transactions which always increasing can cause trouble in data management. The price of the application that is relatively expensive can be a problem for cooperative which don’t have any information system yet. Furthermore, user needs IT expert for maintaining and updating system. Saving and loan information system using SaaS model (Software as a Service) can be a solution to the problem. With the SaaS model users do not need to buy the app, just by subscribing with the application directly to use the application. Saving and loan multi cooperative information system developed for ease the saving and loan data management. Saving and loan multi cooperative information system developed with Extreme Programming method by using PHP languages, and Laravel Framework. The conclusion of this research is saving and loan multi cooperative information system is successfully built according to user needs, by displaying data transparently.